The double-edged sword of CEO narcissism: A meta-analysis of innovation and firm performance implications - Priscilla S. Kraft (Journal of Product Innovation Management, 2022)
Despite a growing body of research, the role of chief executive officer (CEO) narcissism for firm performance is subject to a controversial discussion in the literature. To help advance the discussion, I build on upper echelon theory to propose that innovation is a crucial mediating mechanism that helps explain how CEO narcissism may be beneficial for firm performance. To better understand the conditions under which CEO narcissism may be beneficial for innovation and ultimately firm performance, I investigate the moderating role of CEO gender and managerial discretion. Building on 68 studies, results from meta-analytical structural equation modeling confirm that CEO narcissism can be beneficial for firm performance through stimulating innovation. However, the results further caution that these performance benefits are likely to be canceled out by other detrimental actions pursued by narcissistic CEOs, indicating that they can be a double-edged sword for firms. Moreover, the results support that narcissistic female CEOs engage less in innovation (compared to their male counterparts). Interestingly, they seem to engage in other beneficial actions which ultimately improve overall firm performance, whereas their male counterparts engage in other harmful actions which hurt overall firm performance. The results further highlight that, while the upsides of narcissistic CEOs for performance through innovation increase in high managerial discretion contexts, their greater leeway enhances their downsides even more, so that they do not only offset the benefits of narcissistic CEOs, but even lead to detrimental effects for performance. This study contributes to the literature on CEO narcissism by theorizing and empirically demonstrating that the relationship between CEO narcissism and performance is more complex than previously depicted and requires a more nuanced investigation of the underlying mechanism as well as of potential contingencies. Building on these findings, future research opportunities are identified to further advance the literature on CEO narcissism.
Keywords: 650; CEO narcissism; firm performance; innovation; meta-analysis; upper echelon theory